Hubungan Pajanan Pestisida Dengan Kejadian Hipotiroid Pada Wanita Usia Subur di Daerah Pertanian Hortikultura Desa Gombong Kecamatan Belik Pemalang - Dias Aji Bantarwati; Suhartono Suhartono; Ari Suwondo (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2013)
Background : Thousands of farmers and farm workers were poisoned by pesticides each year. Risk of exposure topesticides in agriculture as well as to women who are involved in agricultural activities, one of them washypothyroidism. Hypothyroidism in the group of women of childbearing age (WCA) can cause reproductivedisorders such as infertility, spontaneous abortion, fetal growth disorders, and premature birth. The researchobjective was to prove that exposure to pesticides is a risk factor for hypothyroidism on WCA in highlandagricultural area Gombong village, Belik subdistrict Pemalang regency.Methods : Cross-sectional study on 34 subjects research at highland agricultural Gombong District Pemalang Regency.Samples were taken by using a systematic Sampling method. Pesticide exposure was measured by asking WCA’s(17-35 years) involved in agricultural activities using structured questionnaire and by checking their level ofcholinesterase. Incidence of hypothyroidism measured using TSH (Thyroid Stimulating Hormone) rate parameter.Confounding variables were also measured. These variables were level of education, BMI, participation in hormonalcontraception, iodine intake, and exposure to cigarette smoke. Data would be analyzed using Chi-Square test at 0,05level of significancy.Result : The prevalence of hypothyroidism among WCA was 2.,4 %.. Pesticide exposure is a risk factor forhypothyroidism; PR 95 % CI = 4.278 ( 1.347-13.581) and p-value=0.015. The higher the degree of exposure, the greaterthe risk of having hypothyroidism. The results showed that there was no correlation between age, level of education,BMI, participation in hormonal contraception, iodine intake, and exposure to cigarette smoke with hypothyroidismon childbearing age woman in highland agricultural area Gombong village, Belik subdistrict Pemalang regency.Conclusion: Pesticide exposure is a risk factor for thyroid dysfunction among WCA in agricultural areas. Keywords: Pesticide exposure, thyroid dysfunction, hypothyroidism.